Highlighting the role of cognitive and brain reserve in the substance use disorder field - Culuti, D; Ladrón de Guevara-Miranda, David; Castilla-Ortega, María Estela; Santín-Núñez, Luis Javier; Sampedro-Piquero, Patricia (Bentham Science Publishers, 2019)
Background: Cognitive reserve (CR) refers to the ability of an individual to cope with brain pathology remaining free of cognitive symptoms. This protective factor has been related to compensatory and more efficient brain mechanisms involved in resisting brain damage. For its part, Brain reserve (BR) refers to individual differences in the structural properties of the brain which could also make us more resilient to suffer from neurodegenerative and mental diseases. Objective: This review summarizes how this construct, mainly mediated by educational level, occupational attainment, physical and mental activity, as well as successful social relationships, has gained scientific attention in the last years with regard to diseases, such as neurodegenerative diseases, stroke or traumatic brain injury. Nevertheless, although CR has been studied in a large number of disorders, few researches have addressed the role of this concept in drug addiction. Methods: We provide a selective overview of recent literature about the role of CR and BR in preventing substance use onset. Likewise, we will also discuss how variables involved in CR (healthy leisure, social support or job- related activities, among others) could be trained and included as complementary activities of substance use disorder treatments. Results: Evidence about this topic suggests a preventive role of CR and BR on drug use onset and when drug addiction is established, these factors led to less severe addiction-related problems, as well as better treatment outcomes. Conclusion: CR and BR are variables not taken yet into account in drug addiction. However, they could give us a valuable information about people at risk, as well as patient’s prognosis.
Author manuscript
Keywords: Neuroplasticidad; Adicción; Drug; Addiction; Cognition; Cognitive reserve; Brain reserve; Neuroplasticity.